2010
DOI: 10.18388/abp.2010_2370
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an antibacterial protein from dried fruiting bodies of the wild mushroom Clitocybe sinopica.

Abstract: A novel antibacterial protein with a molecular mass of 44 kDa has been isolated from dried fruiting bodies of the wild mushroom Clitocybe sinopica. Sodium dodecyl sulfate/polyacrylamide gel electrophoresis showed that the protein was composed of two subunits each with a molecular mass of 22 kDa. Its N-terminal amino-acid sequence, SVQATVNGDKML, has not been reported for other antimicrobial proteins. The purification protocol included ion exchange chromatography on DEAE-cellulose, CM-cellulose and Q-Sepharose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Later studies have shown that certain higher molecular weight peptides and proteins of mushroom species are also taking part in bioactivity. Various antifungal proteins from different fungi such as Clitocybe sinopica, Aspergillus giganteus, Aspergillus niger, Zygosaccharomyces bailii, and Tricholoma giganteum [19,[31][32][33][34] have been reported. An immune modulatory protein LZ-8 from G. lucidum was also proposed to have therapeutic effects on cancer and autoimmune disease [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies have shown that certain higher molecular weight peptides and proteins of mushroom species are also taking part in bioactivity. Various antifungal proteins from different fungi such as Clitocybe sinopica, Aspergillus giganteus, Aspergillus niger, Zygosaccharomyces bailii, and Tricholoma giganteum [19,[31][32][33][34] have been reported. An immune modulatory protein LZ-8 from G. lucidum was also proposed to have therapeutic effects on cancer and autoimmune disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the bacterial growth inhibition at micromolar concentration of different mushroom AMPs has also been investigated earlier. For instance, the proteins purified from Clitocybe sinopica had potential antifungal activity toward Agrobacterium tumefaciens at 0.14-2.7 µM [19]. These proteins had also a broad spectrum of activities against a number of plant pathogenic bacteria including strains of Agrobacterium and Xanthomonas.…”
Section: Marimuthu and Mahendranmentioning
confidence: 99%
See 1 more Smart Citation
“…Its hemolytic activity remained stable at pH 4.0-12.0, but activity was indiscernible at pH 2 and pH 13 and below pH 2 (Ngai and Ng 2006). A dimeric 44-kDa antibacterial hemolysin from mushroom Clitocybe sinopica demonstrated antibacterial activity against Xanthomonas malvacearum, Xanthomonas oryzae, Agrobacterium tumefaciens, A. rhizogenes, and A. vitis, but not against Escherichia coli, Erwinia herbicola, Pseudomonas batatae, and S. aureus, and no antifungal activity against Bipolaris maydis, B. sativum, Fusarium oxysporum, Setosphaeria turcica, and Verticillium dahlia (Zheng et al 2010).…”
Section: Fungal Proteins and Peptides With Antibacterial Activitymentioning
confidence: 99%
“…The CH 2 Cl 2 layer was evaporated under reduced pressure and the resulting residue was chromatographed on silica gel (petroleum ester/ethyl acetate = 2:1) to give the target molecule; yields: 71-80%. The antibacterial activities of the target compounds in vitro were tested via an agar-well diffusion method 20,21 .…”
Section: Synthesis Of Compounds 6 19mentioning
confidence: 99%